Rutile, anatase, brookite and titania thin film from Hubbard corrected and hybrid DFT - Badalov, Sabuhi; Bocchini, Adriana; Wilhelm, Rene; Kozub, A. L.; Gerstmann, Uwe; Schmidt, Wolf Gero (Materials Research Express)
As a benchmark, the structural, electronic and optical properties of the three main phases of TiO$\rm{_2}$ crystals have been calculated using Hubbard U correction and hybrid functional methods in density-functional theory. These calculations are compared concerning the available experimental observations on pristine TiO$\rm{_2}$ crystals. Modified hybrid functionals, particularly the PBE0 functional with 11.4% fraction of exact exchange, are shown to provide highly accurate atomic structures and also accurate electronic structure data, including optical excitation energies. With $\rm{DFT+U}$, accurate optical spectra are also possible, but only if the Hubbard U is applied on the O $\rm2p$ electrons exclusively. Furthermore, both methods, the 11.4%-PBE0 hybrid functional and the $\rm{DFT+U_p}$ scheme have been used to study TiO$\rm{_2}$ amorphous ultra-thin films, confirming the agreement of the two methods even with respect to small details of the optical spectra. Our results show that the proposed $\rm{DFT+U_p}$ methodology is computationally efficient, but still accurate. It can be applied to well-ordered TiO$\rm{_2}$ polymorphs as well as to amorphous TiO$\rm{_2}$ and will allow for the calculations of complex titania-based structures.

DC Ionic Conductivity in KTP and Its Isomorphs: Properties, Methods for Suppression, and Its Connection to Gray Tracking - Padberg, Laura; Quiring, Viktor; Bocchini, Adriana; Santandrea, Matteo; Gerstmann, Uwe; Schmidt, Wolf Gero; Silberhorn, Christine; Eigner, Christof (Crystals)
We study the DC conductivity in potassium titanyl phosphate (KTiOPO4, KTP) and its isomorphs KTiOAsO4 (KTA) and Rb1%K99%TiOPO4 (RKTP) and introduce a method by which to reduce the overall ionic conductivity in KTP by a potassium nitrate treatment. Furthermore, we create so-called gray tracking in KTP and investigate the ionic conductivity in theses areas. A local unintended reduction of the ionic conductivity is observed in the gray-tracked regions, which also induce additional optical absorption in the material. We show that a thermal treatment in an oxygen-rich atmosphere removes the gray tracking and brings the ionic conductivity as well as the optical transmission back to the original level. These studies can help to choose the best material and treatment for specific applications.

Electrochemical performance of KTiOAsO_4 (KTA) in potassium-ion batteries from density-functional theory - Bocchini, Adriana; Gerstmann, Uwe; Bartley, Tim; Steinrück, Hans-Georg; Henkel, Gerald; Schmidt, Wolf Gero (Phys. Rev. Materials)

Oxygen vacancies in KTiOPO_4: Optical absorption from hybrid DFT - Bocchini, Adriana; Gerstmann, Uwe; Schmidt, Wolf Gero (Phys. Rev. B)

Potassium titanyl phosphate Z- and Y-cut surfaces from density-functional theory - Neufeld, Sergej; Bocchini, Adriana; Schmidt, Wolf Gero (Physical Review Materials)